Cryptocarya kaengkrachanensis, a new species of Lauraceae from Kaeng Krachan National Park, southwest Thailand - Zhang, Meng (PhytoKeys, 2020)
Abstract. A new species of Lauraceae, Cryptocarya kaengkrachanensis M.Z.Zhang, Yahara & Tagane, from Kaeng Krachan National Park, Phetchaburi Province, southwestern Thailand, is described and illustrated. This species is morphologically most similar to C. amygdalina in that its leaves are pinnately veined, leathery, and apparently glabrous (but microscopically hairy) abaxially, twigs are yellowish brown hairy, and fruits are 1.36 to 1.85 times longer than width. However, C. kaengkrachanensis is distinguished from C. amygdalina in having the leaves of ovate and elliptic (vs. oblong-lanceolate) with leaf aspect ratio (length:width) from 1.38 to 2.28 (vs. 2.46–3.43), and ovoid fruits (vs. ellipsoid) with stalk distinctly swollen (vs. not or only slightly swollen). In addition, phylogenetic trees constructed based on internal transcribed spacer sequences (ITS) and genome-wide SNPs using MIG-seq showed that C. kaengkrachanensis is not sister to C. amygdalina and is distinct from all the other Cryptocarya species hitherto recognized in Thailand. Analysis including other species demonstrates that C. floribunda should be a synonym of C. amygdalina, but we recognize C. scortechinii as a distinct species.